Cataloguing Of Medicinal Plants In Vellanikkara Rubber Estate - Raghavan KK (Department of plantation Crops and Spices, College of Horticulture, 1992)
The investigation revealed the presence of many medicinal plants growing as undergrowths in the rubber plantation . These plants are widely used by all the sections of the population , whether directly as home remedies or in the medicament of the different indigenous systems of medicines, or indirectly in the pharmaceutical preparation of modern medicine . It can be presumed that the vast area occupied by the rubber plantation industry in our country is richly endowed with a wide variety of plants of medicinal value which represent a great national resources. Indian officially recognizes over 2500 plants as having medicinal value , and it has been estimated that over 6000 plants are used in traditional , folck and herbal medicine , represent a great national resource. Indian officially recognizes over 2500 plants as having medicinal value , and it has been estimated that over 6000 plants are used in traditional , folk, and herbel medicine , representing about 75 per cent of the medicinal needs of the country . Some of these plants are also abundant in rubber plantations. The presence of a large number of weeds having medicinal value under the shade of rubber of weeds having medicinal value under the shade of rubber plantation give influence to fact that they can be cultivated as intercrops in the plantation provided there is internal market demand and fetches a good remunerative profit . This will bring additional income to the lakhs of rubber growers from their limited unit areas. Plants like Hemidesmus indicus and Curculigo Orchioides which find a favourable growth under the dense canopy of rubber , are of much commercial importance . But the impact of cultivation of these plants on the growth and yield of rubber needs investigation . The experiments started at the Rubber Research Institute of India in this line will definitely bring out positive developments in the near future. Further about 80 per cent of the raw materials for drugs used in the Indian system of medicine and homeopathy are based on plant product s. The credibility of these systems of medicine depending available authentic raw materials in sufficient quantities. With some 46,000 licenced pharmacies manufacturing the traditional remedies of these medicinal systems, it is necessary to plan for large scale cultivation of medicinal plants and ensure that they are accurately identified , properly processed , free of adulterants and of acceptable quality . In areas where land is limiting these crops can be cultivated as intercrops can be cultivated as intercrop. More over this will be an indirect attempt for the conversation of the endangered plants of medicinal importance.